1960
DOI: 10.1002/aic.690060117
|View full text |Cite
|
Sign up to set email alerts
|

The effects of superheat and surface roughness on boiling coefficients

Abstract: The effects of liquid superheat and surface roughness on boiling coefficients were investigated in a series of experiments in which water, acetone, n-hexane, carbon tetrachloride, and carbon disulfide were boiled on a flat plate. In addition to the usual thermal measurements, the number of active boiling centers was determined, whenever possible, by visual means, and a quantitative measure of surface roughness was made. It was found that the number of active boiling centers on the plate increased with increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

1960
1960
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(54 citation statements)
references
References 12 publications
3
51
0
Order By: Relevance
“…Jakob [15], who first studied the effect of surface roughness on the boiling of water, found that a surface with a square grid of machined grooves improved boiling heat transfer by approximately 300% compared to a smooth surface. Similar conclusions were reached by other researchers who used emery paper [16] and electrical discharge machining (EDM) [17] as surface roughening methods. A wide variety of fluids have been investigated for surfaces with various degrees of roughness, all showing that the cavities generated during roughening processes serve as nucleation sites [18,19].…”
Section: Introductionsupporting
confidence: 86%
“…Jakob [15], who first studied the effect of surface roughness on the boiling of water, found that a surface with a square grid of machined grooves improved boiling heat transfer by approximately 300% compared to a smooth surface. Similar conclusions were reached by other researchers who used emery paper [16] and electrical discharge machining (EDM) [17] as surface roughening methods. A wide variety of fluids have been investigated for surfaces with various degrees of roughness, all showing that the cavities generated during roughening processes serve as nucleation sites [18,19].…”
Section: Introductionsupporting
confidence: 86%
“…Beginning from Jakob [6], Kruzhilin [58] and Rohsenow [59] and further [60][61][62][63][64][65][66][67][68][69][70][71][72][73] main line of development of boiling heat transfer theory is based at approaches connecting HTC to intensity of certain cooling mechanism (an actor) or certain combination of different cooling mechanisms (actors). In this connection these approaches are subsumed under the category dubbed as a model of "the theatre of actors" (MTA).…”
Section: Mta and Mtdmentioning
confidence: 99%
“…(1) Surface modification by increasing surface roughness, 9 coating with microstructures 10 or nanostructures, 11 or using nanoparticle suspension (nanofluids) 12,13 which results in deposition of nanoparticles on the surface, etc. Such modification generally increases surface wettability, which causes an increased CHF through the enhanced liquid spreading over the heated area.…”
mentioning
confidence: 99%